2021
DOI: 10.1038/s43247-021-00224-5
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of wet mantle wedge by self-promoting carbonation

Abstract: More than one teramole of carbon per year is subducted as carbonate or carbonaceous material. However, the influence of carbonation/decarbonation reactions on seismic activity within subduction zones is poorly understood. Here we present field and microstructural observations, including stable isotope analyses, of carbonate veins within the Higuchi serpentinite body, Japan. We find that the carbon and oxygen isotope compositions of carbonate veins indicate that carbonic fluids originated from organic materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 82 publications
0
22
0
Order By: Relevance
“…If our predictions are correct, the common decoupling‐coupling transition along the plate interface in warm subduction zones would be difficult to explain with the breakdown of talc, since its formation via Si‐metasomatism seems to be limited to a restricted set of environmental conditions. Alternatively, much of the talc may form via mineral carbonation rather than Si‐metasomatism (Okamoto et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…If our predictions are correct, the common decoupling‐coupling transition along the plate interface in warm subduction zones would be difficult to explain with the breakdown of talc, since its formation via Si‐metasomatism seems to be limited to a restricted set of environmental conditions. Alternatively, much of the talc may form via mineral carbonation rather than Si‐metasomatism (Okamoto et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This elevated fluid pressure deemed responsible for ETS around the mantle wedge corner is caused by localized slab dehydration and silica precipitation, which is favorable in warm‐slab environments (Audet & Bürgmann, 2014; Fagereng et al., 2018; Tulley et al., 2022). In addition to dehydration of hydrous minerals in the subducting slab, mixing of compositionally disparate rocks under highly reactive and fluid‐saturated conditions can cause metasomatic reactions that may change mineralogy (and therefore rheology) and/or release fluid, leading to brittle failure at conditions consistent with the source region of deep tremor in subduction zones (Angiboust et al., 2015; Bebout, 2007; Bebout & Penniston‐Dorland, 2016; Okamoto et al., 2021; Tarling et al., 2019). In these mixed lithology (and therefore rheology) assemblages, ETS has been explained by contemporaneous failures in velocity‐weakening materials and viscous shear in surrounding velocity‐strengthening matrix (Ando et al., 2012; Beall et al., 2019; Behr et al., 2018; Fagereng et al., 2014; Hayman & Lavier, 2014; Skarbek et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…•OH oxidises even graphite (Wang and Zhang, 2018), a common product of the thermal maturation of organic compounds in metamorphic rocks, and may therefore degrade fault zones containing such minerals and materials. In natural examples, degradation or consumption of graphite has been observed in some fault zones (Nishiyama et al, 1990;Kretz, 1996;Nakamura et al, 2015), and the involvement of oxidising fluids in these processes has been suggested (Nishiyama, 1990;Okamoto et al, 2021). In addition to mechanical processes, oxidative corrosion could promote such graphite degradation.…”
Section: Discussionmentioning
confidence: 99%